The Cervical Vertebral Bone Quality Score Is a Novel Reliable Index Reflecting the Condition of Paraspinal Muscles and Predicting Loss of Cervical Lordosis After Open‐Door Laminoplasty - Junhu Li; Xingxia Long; Linnan Wang; Qiujiang Li; Lei Wang; Yueming Song (Orthopaedic Surgery)
ABSTRACT Objective Recently, the MRI‐based cervical vertebral bone quality (C‐VBQ) scoring system has demonstrated accuracy in reflecting cervical bone quality and predicting postoperative complications from cervical spine surgery. Studies have shown that cervical bone quality is closely linked to loss of cervical lordosis (LCL) after open‐door laminoplasty. Additionally, research on lumbar VBQ indicates a strong correlation between lumbar VBQ scores and lumbar paraspinal muscle quality. However, the relationship of C‐VBQ score to cervical paraspinal muscles and LCL remains unclear. Therefore, this study aimed to explore the relationship between C‐VBQ score and cervical paraspinal muscle‐related parameters as well as postoperative LCL, in addition to exploring the risk factors associated with LCL. Methods A total of 101 patients who underwent standard C3–C7 open‐door laminoplasty at our institution from 2012 to 2022 were included in this study. The LCL group was defined as loss of cervical lordosis > 5° at 1‐year postoperative follow‐up. Cervical X‐rays were obtained to measure the C2–7 Cobb angle, C2–7 sagittal vertical axis (SVA), T1 slope, and cervical range of motion (ROM). The relative cross‐sectional area (RCSA) and degree of fat infiltration (DFF) of the deep cervical extensors, flexors, and all muscles were measured using image J software. Cervical CT Hounsfield unit (HU) and C‐VBQ values were measured on preoperative CT and MRI T1‐weighted mid‐sagittal images, respectively. Then, demographics, cervical sagittal parameters, ROM, paraspinal muscle‐related parameters, CT‐HU and C‐VBQ values were assessed for their correlation with LCL, and multivariate linear analysis was used to determine the risk factors associated with LCL. Finally, the relationship between C‐VBQ scores and cervical paraspinal muscle‐related parameters was evaluated. Results A total of 55 (54.45%) patients were included in the LCL group due to loss of cervical lordosis > 5° at 1‐year follow‐up. LCL was positively correlated to the preoperative T1 slope, Flexion ROM, C2–7 ROM, Flexion/Extension ROM, Flexion muscles DFF, Extension muscles DFF, Average DFF, and C‐VBQ scores, while it was negatively correlated to Extension ROM, Extension muscles RCSA, Total RCSA, and CT‐HU values. Furthermore, Flexion/Extension ROM, Total RCSA, Average DFF, CT‐HU, and C‐VBQ values were independent risk factors for LCL. In addition, C‐VBQ scores were significantly correlated with RCSA and DFF of Flexion and Extension muscles. Conclusions This study is the first to find a significant correlation between C‐VBQ scores and cervical paraspinal muscle quality. The C‐VBQ score is a comprehensive indicator that reflects the quality of the cervical bone and paravertebral muscles, and it is a novel predictor of LCL after open‐door laminoplasty.